Lessons learned in post-pandemic: Implications of teleworking for technology-based professionals in Costa Rica - Silva Atencio, Gabriel; Morgan Asch, Jesus (LACCEI, 2024)
This article addresses the analysis of the influence of teleworking on technology professionals in Costa Rica as an effect of the current situation. Dialogues with experts on the subject and a detailed study of the literature expose trends in work modalities, emphasizing remote and mixed forms and examining their impact on work efficiency, well-being, and the economy. The increase in the adoption of remote approaches is highlighted both by international and national firms. Monetary and savings advantages are identified, as are associated concerns, such as a sedentary lifestyle and isolation. In addition, the importance of organization and adaptability is underscored, along with the need to maintain spaces for collaboration. Suggestions are provided to adjust to these changes and take advantage of this new work model’s opportunities in a competitive and constantly changing environment.